Optimizing Household-Scale Fish Farming Wastewater Management As A Form Of Environmental Conservation In Densely Populated Areas - Alghifari, Abizar; Ningsih, Ira Rahayu; Sari, Widiya Permata; Ikhsan, Muhammad Fathan Nur; Ramdhani, Syahrul; Rochiandani, Anasthasia Rizky; Nurmiati, Evy (SEAN Institute, 2024)
One of the strategies to improve the standard of living of the Bakti Jaya people is the innovative home-scale fish farming owned by Mr. Budi. Located in the middle of a populous area, the water management system in aquaculture is an important thing to consider so as not to pollute the environment. Therefore, this research aims to analyze the wastewater management of home-scale fish farming in the context of environmental conserva-tion carried out by Pak Budi's BP Farm, as well as to ex-plore the positive impacts that can be generated from waste management in densely populated areas. This research uses a qualitative descriptive method. The re-sults showed that the wastewater management system applied by BP Farm fish farming can be an alternative that utilizes traditional tools, but the system can be fur-ther maximized by applying the RAS system so that the waste water produced becomes less. In addition, the wastewater produced by BP Farm fish farming has a positive impact, that is, it can be used for liquid fertilizer which contains nutrients that are good for plants.